PENGARUH LOVE OF MONEY, RELIGIUSITAS, DAN IDEALISME TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Fachrizal, Mohamad; Haris, Nurhayati; Indriasari, Rahayu (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2020)
This research aims to evaluate and analyze the effect of love of money, religiosity and idealism to ethical perception of accounting student. This type of research is survey research. The research method used in this study is quantitative research. Data analysis techniques using descriptive analysis and multiple linear regression. The results shown that how simultaneous love of money, religiosity and idealism has an significant effect to ethical perception of accounting student. Love of money has a significant effect to ethical perception of accounting student. Religiosity has a significant effect to ethical perception of accounting student. Idealism has a significant effect to ethical perception of accounting student. Suggestions in this study are for all accounting students at Tadulako University by improving perception and ethics. Given the ethical issues are one of the important factors needed in the teaching and learning process and the profession.